Random access control schemes for massive machine type communications in cellular IOT networks - Althumali, Huda Dakhilallah A (2022)
Machine Type Communications (MTC) refer to the autonomous interaction between connected devices without human intervention. The deployment of MTC on cellular networks provides ubiquitous services to Internet-of-Things (IoT) systems. Recently, the Third-Generation Partnership Project (3GPP) introduced the standard specifications of deploying MTC on cellular networks. The 3GPP recommends the recent cellular networks such as Long-Term Evolution (LTE), LTE-Advanced (LTE-A) and Fifth-Generation (5G) networks as an appropriate infrastructure for MTC due to wide coverage, scalability, low latency and spectral efficiency. Indeed, with an increased number of devices connecting to the network everyday, massive numbers of machine devices are expected to simultaneously access the network resources especially during emergency scenarios. This massive access results in excessive congestion and collisions in the random access channel (RACH) which is considered the first step to access network resources. These massive collisions cause the devices to be blocked from accessing network resources which results in performance degradation for the overall MTC system. For this reason, it is important to improve random access (RA) control schemes to accommodate the increased number of machine devices connecting to the network. In this thesis, RA control schemes are classified according to targetted objectives into three categories: (1) massive access control schemes, (2) energy efficiency schemes and (3) performance improvement schemes. Each category is further divided into two subcategories, and the relevant RA schemes are presented for each category. Furthermore, an analytical comparison has been provided among the different schemes according to several performance parameters. This work mainly focuses on the massive access control schemes which are sub-divided into congestion control and collision resolution schemes. In order to increase the access success rate during massive access scenarios, this work proposes a new dynamic backoff collision resolution scheme (DBCR) for delay-tolerant devices. In this scheme, the RACH collisions are resolved using a backoff procedure which dynamically adjusts the backoff indicator (BI) based on the number of backlog devices and available resources. The proposed scheme is integrated with three well-known random access schemes. The mathematical analysis of the DBCR and derivation of the optimal value of BI is presented for the three different combinations. Thereafter, extensive simulations are performed to evaluate the proposed scheme. The analysis and simulation results demonstrate that the DBCR scheme achieves an access success rate of 99.9% with a slight increase in access delay which is reasonable for delay-tolerant applications during massive arrivals scenarios. Further, this work introduces a dynamic tree splitting (DTS) scheme to resolve RACH collisions for delay-sensitive devices during burst arrival scenarios. The DTS scheme assigns a specific number of resources/preambles to the collided group of devices for their next access attempt with the aim of reducing access delay. The number of preambles assigned for each group is determined based on the mean number of collisions in each random access opportunity (RAO) in order to increase the utilisation of preambles. The mathematical analysis of the proposed scheme is presented and the access delay is derived. The analysis and simulation results show that the DTS reduces the access delay by approximately 12% compared to the recent benchmarks, with a very low drop rate, which indicates the efficiency and reliability of the proposed scheme. Furthermore, a priority-based load-adaptive preambles separation (PLPS) RA scheme for quality-of-service (QoS)-differentiated applications in 5G networks is proposed. In this scheme, three classes of devices are considered. These are devices with enhanced mobile broadband (eMBB), ultra-reliable low latency communication (URLLC) and massive machine type communication (mMTC). The available number of preambles is divided into three groups, and the number of preambles is assigned for each group based on class priority and load intensity. The mathematical analysis of the proposed scheme is presented along with the derivations of several performance metrics. The analysis and simulation results show that the PLPS scheme succeeds in achieving the targetted QoS requirements for each class even for a large number of devices, which is very promising for the 5G heterogeneous services.